A comparison of postoperative blood lactate concentrations and kinetics in cardiac surgical patients being and not being administered metformin - Fotini Ampatzidou; Konstantinos Diplaris; Odysseas Drosos; George Drossos (Journal of Medical Science, 2022)
Aim. Early discontinuation of metformin before cardiac surgery is advised by several national societies, although no hard evidence exist supporting this practice. This precaution is mostly extrapolated by data on different clinical settings. The aim of this study is to investigate the impact of preoperative metformin use on lactate concentrations and lactate clearance during the first postoperative day following cardiac surgery.